Diet and nutrition sourcebook basic consumer health information about dietary guidelines, servings and portions, recommended daily nutrient intakes and meal plans, vitamins and supplements, weight loss and maintenance, nutrition for different life stages and medical conditions, and healthy food choices along with details about government nutrition support programs, a glossary of nutrition and dietary terms, and a directory of resources for more information - Larsen, Laura (Gale Virtual Reference Library, 2011)
Provides up-to-date guidance on nutrition and health and details how children, seniors, vegetarians, athletes, and others can benefit from good nutrition.